Comfort with uncertainty in primary care practice: lessons learned from a pilot study with psychology students. - Ogbeide, Stacy A.; Murphy, Bridget (Journal of Integrated Care, 2025)
Purpose: Our goal was to assess how comfort with uncertainty (CwU), a variable connected to success in primary care physicians, was associated with readiness to perform tasks in integrated primary care. As behavioral health integration in primary care continues to grow, understanding the variables that encourage or discourage behavioral health learners entering primary care are of great importance to meet workforce demands. Design/methodology/approach: A sample (N = 35) of graduate students enrolled in doctoral, health service psychology programs completed a survey of demographics, two CwU measures, and a measure of readiness for specific integrated primary care tasks as well as measures of resilience and psychological flexibility. Findings: Results found that CwU was significantly, positively associated with more readiness to use the following primary care-specific skills over and above level of training: consulting with medical staff (p = 0.039), accepting warm handoffs (p = 0.031), conducting shared medical visits (p = 0.034), scheduling patients within existing medical appointments (p = 0.05), and educating patients about their medical disorder and advise self-management strategies (p = 0.049). Originality/value: These findings suggest that CwU may be an important variable to consider in integrated primary care trainees.